Hot-melt pressure-sensitive adhesive for seamless bonding of nylon fabric Part II: Process parameter optimization for seamless bonding of nylon fabric. Issue 12 (June 2019) - Kuo, Chung-Feng Jeffrey; Lan, Wei Lun; Wang, Jui-Wen; Chen, John-Ber; Lin, Pin-Hua
This study develops hot melt pressure sensitive adhesives (HMPSAs) for the seamless bonding of nylon fabric, using butyl acrylate as the main monomer material and mixing the functional monomer for polymerization. It is combined with 2-10phr diphenyl (2, 4, 6-trimethylbenzoyl) phosphine oxide for the photoinitiator and ultraviolet irradiation is used to make a pre-polymer. The effects of butyl acrylate content, type of functional monomer, and 2-10phr diphenyl (2, 4, 6-trimethylbenzoyl) phosphine oxide content on the molecular weight of acrylate pre-polymer are discussed, following the Taguchi method. The pre-polymer is then mixed with the reactive diluent glycidyl methacrylate blend and with 2-10phr diphenyl (2, 4, 6-trimethylbenzoyl) phosphine oxide, coated on a release film, irradiated by ultraviolet light, and cured into hot melt pressure sensitive adhesives. The adhesive properties of hot melt pressure sensitive adhesive bonding on nylon include the peel strength, the shear strength, adhesive warpage, adhesive color difference, and adhesive overflow, which are discussed following the Taguchi method and the elimination and choice translating reality method for multi-quality analysis. Hot melt pressure sensitive adhesives are implemented by optimization parameters for practical validation. The results show that the peel strength of hot melt pressure sensitive adhesives is 1.495 kg/cm, the shear strength of hot melt pressure sensitive adhesives is 14.326 kg/cm 2, adhesive warpage is 0.93 mm, adhesive color difference is 1.66, and adhesive overflow is 0.97 mm. The performance of HMPSAs in this study is enhanced effective.